Changing the Rural Way of Life - Zulfikarovich, Umarov Otabek (European Journal of Life Safety and Stability (2660-9630), 2023)
The reconstruction of the village is impossible without changing the traditional way of life of the rural population, which is understood as a system of activities carried out by the population, determined by the external environment and the specific characteristics of the rural population. The main direction of improving labor in social production will be the further acceleration of the industrialization of agriculture. In modern conditions, personal subsidiary farming is an objective necessity, as it serves as one of the sources of life support. The ability to manage one’s own household is an important advantage of rural life, allowing even large, and numerous families to maintain sufficient material well-being at very low wages in social production. The emergence of new complex techniques that replace manual labor with machine labor in the countryside requires special knowledge.